THE INFLUENCE OF LOCAL GOVERNMENT FINANCIAL PERFORMANCE ON THE ACCOUNTABILITY OF REGIONAL FINANCIAL REPORTING (AN EMPIRICAL STUDY ON CITY/REGENCY GOVERNMENTS IN EAST JAVA PROVINCE FOR THE 2021–2023 PERIOD) - Wijayanti, Rahma Rina; Rahmawati, Siti Nur Ameilia; Kusumawati, Rida; Roselitha, Sherilliya; Puspita, Dela (Media Inovasi Pendidikan dan Publikasi, 2025)
This study examines the effect of financial performance on the accountability of local government financial reporting in East Java Province during the 2021–2023 period. Using a descriptive quantitative approach and secondary data from audited financial reports by the Audit Board of Indonesia (BPK), financial performance was measured through solvency, revenue effectiveness, and spending efficiency, while accountability was proxied by audit opinions. The results show that revenue effectiveness has a significant impact on accountability, while solvency and spending efficiency do not. These findings highlight the importance of fiscal capacity and good governance in building accountable financial reporting.